PENGARUH MODUL FISIKA MULTIMEDIA INTERAKTIF BERBANTUAN GAME DALAM MODEL PROBLEM BASED LEARNING TERHADAP CRITICAL THINKING SKILL SISWA KELAS X SMAN 4 PADANG - Furkana Aulia; Djusmaini Djamas; Ramli Ramli (PILLAR OF PHYSICS EDUCATION, 2017)
One  of humans quality is to have the ideal critical thinking skills. in fact, critical thinking skills of students still have not reached the ideal category. Critical thinking skills can be trained by physics. One solution to develop students' critical thinking skills is the use of teaching materials that use media such as interactive multimedia modules aided game and  problem-based learning model. Purpose of this research is to found the influence of interactive multimedia modules aided game against the students' critical thinking skills. Type of this research is a quasi-experimental, research design with randomized control group only design. As the object of this study is to learn the material by using interactive multimedia module in a game-aided model of problem-based learning. The results showed that the working hypothesis which states that "there is a significant impact physics module-assisted interactive multimedia games in the model problem based learning to critical thinking skills class X SMA 4 Padang" acceptable in the significant level of 0.05 with the contribution of interactive multimedia modules aided game amounting to 32.51%. Then, module-assisted interactive multimedia game physics can be applied by teachers during the process of learning physics